Contribution of Government Expenditure and Distribution of Zakat, Infaq, Sadaqah (ZIS) Funds to Poverty Alleviation in Central Java Province - Khofifah Ghomzah; Slamet Khilmi (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2025)
Poverty is a worldwide concern that must be handled, especially in developing countries like Indonesia, which has serious poverty issues. One of the provinces in Indonesia with a high poverty rate is Central Java Province. This study aims to determine the effect of government expenditures on education, health, and social welfare, as well as the distribution of ZIS funds on poverty in Central Java Province for the period 2017-2024. The data used in this study is time series data that has been processed using the ECM method with the help of E-Views 12 software. The results show that in the long term, government expenditure on education, government expenditure on social welfare, and ZIS funds have a negative and significant effect on poverty. Meanwhile, government expenditure on health has positive and significant on poverty. In the short term, government expenditure on education has no effect on poverty. Government expenditure on health has a positive and significant effect on poverty. Government expenditure on social welfare and the distribution of ZIS funds have a negative and significant effect on poverty.